Worship in the Shadow of Capital: Neoliberalism and the Fate of Religious Freedom in Indonesia - Syahwal, Syahwal (The Indonesian Journal of International Clinical Legal Education, 2025)
This article examines how neoliberal logic influences the articulation and implementation of the right to freedom of religion in Indonesia. Through a non-doctrinal approach and critical analysis of legal frameworks and institutional practices, it demonstrates that neoliberalism not only permeates the economic sphere but also redefines human rights, including religious freedom. Under the neoliberal regime, religious freedom is reduced to an individual preference subject to market logic and commodified within the frameworks of consumption and political stability. The state tends to adopt a passive or selective stance in protecting religious groups, privileging those aligned with dominant economic-political interests while restricting those perceived as disruptive to stability or oppositional to the status quo. Religious freedom is thus politicized, used as a tool for regime legitimacy, and controlled through administrative, symbolic, and economic mechanisms. This article highlights that genuine religious freedom cannot be realized without inclusive democracy, social justice, and the protection of pluralism. Therefore, structural efforts are necessary to liberate religious freedom from neoliberal constraints so that this right can be substantively and equitably exercised within Indonesia’s pluralistic society.